Transforming teen behavior : parent-teen protocols for psychosocial skills training - Cook, Mary Nord (London ; San Diego, CA : Academic Press, an imprint of Elsevier, 2015)
Transforming Teen Behavior: Parent-Teen Protocols for Psychosocial Skills Training is a clinician's guide for treating teens exhibiting emotional and behavioral disturbances. Unlike other protocols, the program involves both parents and teens together, is intended for use by varied provider types of differing training and experience, and is modular in nature to allow flexibility of service. This protocol is well-established, standardized, evidence-based, and interdisciplinary. There are 6 modules outlining parent training techniques and 6 parallel and complementary modules outlining psychosocial skills training techniques for teens. The program is unique in its level of parent involvement and the degree to which it is explicit, structured, and standardized. Developed at Children's Hospital Colorado (CHCO), and in use for 8+years, the book summarizes outcome data indicating significant, positive treatment effects.
Introductions and GuidelinesReview; Treatment Goals: Individual and Family; Feelings: Good, Bad, and Ugly Ones; Feelings Overview; Ambivalence or Mixed Feelings; Feelings Vocabulary; Feeling Intensities; Feelings Identification and Somatic Monitoring; "Fight-or-Flight" Response; Threat in Eye of Beholder; Lowering Arousal; Contagiousness of Feelings; Enmeshment; Interrupting Cycles of Arousal Escalation; Nonverbal Calming Techniques; "Taming Bambi" Metaphor; "What About My Teen?" Examples; Feelings Triggers; Interpersonal Boundaries; "What About My Teen?"; Family Homework.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Adolescent psychology; Teenagers -- Mental health; Parent and teenager; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Adolescent psychology; Parent and teenager; Teenagers -- Mental health; Adolescent Behavior; Parent-Child Relations; Psychology, Adolescent; Adolescent; Child; Humans; Electronic books; Electronic books